2023
DOI: 10.3748/wjg.v29.i2.378
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards the use of histological assessments in ulcerative colitis by gastroenterologists vs pathologists

Abstract: BACKGROUND Histological remission is increasingly accepted as a treatment endpoint in the management of ulcerative colitis (UC). However, the knowledge of histology guidelines and the attitudes towards their use in clinical practice by gastroenterologists and pathologists is unknown. AIM To evaluate the knowledge of histology guidelines and attitudes towards the use of histology in UC by gastroenterologists and pathologists. METHODS A prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…These features seem to indicate that the unbiased real‐world application of the scores, particularly histological ones, is lower. Indeed, another recent survey from Australia 11 reached slightly different conclusions when compared with the survey discussed here. Indeed, in this cohort of 89 gastroenterologists (from which, 30% self‐reported as subspecialists in IBD), <8% reported the use of a systematic histologic scoring system and <12% were certain of the proposed remission cut‐offs.…”
contrasting
confidence: 75%
“…These features seem to indicate that the unbiased real‐world application of the scores, particularly histological ones, is lower. Indeed, another recent survey from Australia 11 reached slightly different conclusions when compared with the survey discussed here. Indeed, in this cohort of 89 gastroenterologists (from which, 30% self‐reported as subspecialists in IBD), <8% reported the use of a systematic histologic scoring system and <12% were certain of the proposed remission cut‐offs.…”
contrasting
confidence: 75%
“…Although histological assessment with the establishment of validated scoring systems, as described above, has made progress during the last years [ 3 ], many histological scoring systems do not consider all relevant aspects of IBD pathology, for example, basal plasmacytosis [ 16 , 17 , 23 ] and histological assessment as well as the fact that correct the usage of scoring systems requires highly experienced IBD pathologists [ 16 , 47 ]. Furthermore, it was recently shown that knowledge of IBD histological scoring systems and their utilization is poor amongst gastroenterologists and pathologists, despite recognition of their importance [ 48 ]. Therefore, quantitative, reliable, time-efficient, and automatable tools in terms of digital pathology are desired, which might be capable of assessing histological inflammation independently, as an additional support to the classic histological assessment that is performed by a pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…With this consideration in mind, we should accept the real-world struggles of proper histopathology score knowledge and proper reporting. In a recent survey from Australia, only around 10% of pathologists reported the use of a systematic histologic scoring system, and more than 80% lacked awareness regarding the definition of remission according to different scoring systems [ 18 ].…”
Section: Introductionmentioning
confidence: 99%